2004
DOI: 10.1177/153537020422900611
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Low-Density Lipoprotein and Chylomicron Remnants on Lipid Accumulation in Human Macrophages

Abstract: The effects of low-density lipoprotein (LDL) and chylomicron remnants on lipid accumulation in human monocyte-derived macrophages (HMDMs) and in macrophages derived from the human monocyte cell line THP-1 were compared. The HMDMs or THP-1 macrophages were incubated with LDL, oxidized LDL (oxLDL), chylomicron remnant-like particles (CMR-LPs), or oxidized CMR-LPs (oxCMR-LPs), and the amount and type of lipid accumulated were determined. As expected, the lipid content of both cell types was increased markedly by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 53 publications
(46 reference statements)
7
62
2
Order By: Relevance
“…1, 6). These findings are in agreement with previous reports suggesting that incubation of macrophages with TG-rich chylomicron remnants and VLDL promotes TG and FFA accumulation to a greater extent (32) than CEs, which are known to accumulate upon acetylated and oxidized LDL treatment (9,32).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1, 6). These findings are in agreement with previous reports suggesting that incubation of macrophages with TG-rich chylomicron remnants and VLDL promotes TG and FFA accumulation to a greater extent (32) than CEs, which are known to accumulate upon acetylated and oxidized LDL treatment (9,32).…”
Section: Discussionsupporting
confidence: 83%
“…TGs in fasting plasma are carried in VLDLs, and these VLDLs have been found within human and experimental atherosclerotic lesions (3,4), providing a rationale to study their direct effects on macrophage functions such as foam cell formation and inflammation. It is well established that VLDL causes the accumulation of TGs and FFAs in macrophages (5)(6)(7)(8)(9). This can occur through three different mechanisms: 1) uptake of intact VLDL particles; 2) uptake of VLDL remnants resulting from lipoprotein lipase-mediated lipolysis; and 3) uptake of FFAs produced by VLDL lipolysis, which can be taken into cells through both passive diffusion and receptor-mediated mechanisms.…”
mentioning
confidence: 99%
“…No study has previously reported the effect of Toll-like receptor 4 activation on individual molecular species of CEs and the magnitude of the increase of saturated and monounsaturated CEs. Oxidized LDL has been reported to cause a significant accumulation of CEs in THP-1 macrophages, as measured by the incorporation of [ 3 H]oleate into CEs separated by TLC (35). However, there has been no report of individual molecular species of CE changing during transformation of the THP cell into more foam-like cells.…”
Section: Discussionmentioning
confidence: 93%
“…However, oxidized or acetylated LDL could promote foam cell formation as they were bound by various scavenger receptors that were not downregulated. Unmodified ␤-VLDL was found to induce foam cell formation without the need for further modification (115,214). Since these studies, a number of additional LDL modifications, many without oxidation, have been shown to also suffice for foam cell formation (1727).…”
Section: B Lipoprotein Retention and Modificationmentioning
confidence: 99%